Predisposing factors for allogeneic blood transfusion in patients with rheumatoid arthritis undergoing primary unilateral total knee arthroplasty - Wang, Xiaolin; Zhang, Liang; Li, Hongchao; Bian, Tao; Zhou, Yixin; Li, Yujun (Frontiers in Surgery, 2023)
To determine the incidence and identify the predisposing factors for allogeneic blood transfusion (ABT) in patients with rheumatoid arthritis (RA) undergoing primary unilateral total knee arthroplasty (TKA).Methods: A total of 702 patients with RA who underwent primary unilateral TKA between 2003 and 2022 at a single center, were retrospectively enrolled. Patients were stratified into the ABT and non-ABT groups. Data on patient demographics, laboratory parameters, and disease-and surgery-related parameters were collected from chart reviews and compared between the ABT and non-ABT groups. Multivariate logistic regression analysis was conducted to identify the possible factors associated with postoperative ABT.Results: A total of 173 (24.6%) patients underwent ABT after surgery. Significant risk factors for ABT included the degree of flexion contracture (odds ratio (OR)=1.018, P=0.005) and thickness of insertion (OR=1.170, P=0.014). Conversely, body mass index (OR=0.937, P=0.018), preoperative hemoglobin level (OR=0.973, P<0.001), and intraoperative use of tranexamic acid (TXA) (OR=0.119, P<0.001) were associated with a lower risk of ABT in TKA.We identified the significant risk and protective factors for ABT during TKA in patients with RA. This information could be helpful in optimizing perioperative blood management strategies during these surgeries.